Proceedings of the First ACM SIGCHI Annual Symposium on Computer-Human Interaction in Play 2014
DOI: 10.1145/2658537.2658686
|View full text |Cite
|
Sign up to set email alerts
|

Screen ecologies, multi-gaming and designing for different registers of engagement

Abstract: In this paper, we propose the notion of screen ecologies and argue for its importance in the study of contemporary digital game play. We draw on findings from a range of studies to highlight the interplay between screen ecologies, game design, and registers of engagement. We discuss how game play is increasingly mediated by multiple screen configurations, and in turn, how the design of different games are suited to or appropriated within these different screen ecologies. From this analysis we propose a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Although concepts like "immersion" tend to convey the idea of a player being completely absorbed in their current activity in a virtual world, we found that in fact that many SL players multitasked: combining SL use with offline activities or engaging simultaneously in multiple conversations within SL (see Carter, Nansen, & Gibbs, 2014, for recent research into multitasking in the gaming context). Informants felt that text suited this: "When you're multitasking as I often am, text is easier."…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Although concepts like "immersion" tend to convey the idea of a player being completely absorbed in their current activity in a virtual world, we found that in fact that many SL players multitasked: combining SL use with offline activities or engaging simultaneously in multiple conversations within SL (see Carter, Nansen, & Gibbs, 2014, for recent research into multitasking in the gaming context). Informants felt that text suited this: "When you're multitasking as I often am, text is easier."…”
Section: Resultsmentioning
confidence: 89%
“…Performance construction is particularly apparent when players exploit lean media to multitask and multigame (Carter et al, 2014), engaging in impression management and multiple conversations with a range of people both online and physically collocated (Jones, 2002). Multitasking need not imply deception of a malicious kind.…”
Section: Discussionmentioning
confidence: 99%
“…Though there are many other cases where second screens complement another leisure activity (e.g., in the world of video games [18,28]), TV is the primary focus of the HCI community, and many ethnographic studies document just how nuanced and far-reaching this use case is. This research has most commonly taken the form of in-situ studies of second screeners in their homes.…”
Section: Second Screeningmentioning
confidence: 99%
“…However, other methods are necessary for ensuring that game sessions last for a long time. Exploiting recent research on designing game play rhythms that can facilitate "multigaming," [3] or the simultaneous playing of multiple games, has the potential to address this challenge.…”
Section: Measuring Fine Player Movementsmentioning
confidence: 99%
“…Carter, Nansen and Gibbs [3] describe the context that facilitates this multi-gaming experience. "Rather than a single screen sitting on a table capturing the full attention of the user, the modern computing experience is commonly much more complex and distributed across multiple devices."…”
Section: Measuring Fine Player Movementsmentioning
confidence: 99%